Research on the Impact of the Digital Economy on Regional Innovation - Yue, Qin (Asia Pacific Economic and Management Review, 2026)
As a new type of economy following the agricultural and industrial economies, the digital economy is reshaping the regional innovation landscape through the non-competitive nature of data elements, the strong penetration of digital technologies, and the network externalities of platform ecosystems. Based on data from 31 provinces in mainland China from 2011 to 2023, this paper constructs a two-way fixed effects model to analyze the impact and mechanisms of the digital economy on regional innovation capabilities. The study shows that: (1) the digital economy significantly promotes the enhancement of regional innovation capabilities; (2) the moderation effect analysis further indicates that government support plays a positive moderating role in the relationship between the digital economy and regional innovation capabilities; (3) the heterogeneity analysis reveals that the positive impact of the digital economy on regional innovation capabilities exhibits significant regional differences: its innovation-promoting effect is significantly positive in the eastern region, while the effect is relatively weaker in the central and western regions. This paper enriches research on how the digital economy empowers the enhancement of regional innovation capabilities and provides valuable insights and decision-making references for regional innovation breakthroughs.